Pengaruh Employee Engagement Terhadap Kinerja Karyawan Dengan Moderasi Karakteristik Generasi Karyawan Pada Instansi Swasta - Amrina, Elita; Foci, Nia Arfina; Hasan, Alizar (Jurnal Rekayasa Sistem Industri, 2024)
Employee engagement is an important issue that is the main concern of the organization's leaders in managing its employees. The changing characteristics of the employee generation are becoming a specific challenge for human resource management. Employees who are engaged with their work will exert all their abilities, efforts, and thoughts and significantly contribute, where the engagement and personal characteristics possessed by employees in carrying out their work can directly impact their performance. This study aimed to analyze employee engagement's effect on employee performance by moderating the generational characteristics of private agency employees in the City of Padang, West Sumatra. Data was collected through questionnaires distributed to 100 employee respondents working in private institutions in the city of Padang, with purposive sampling technique. Then, the data is processed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. The results of this study indicate that employee engagement generational characteristics (Y and Z generation) have a positive and significant effect on employee performance. Generational characteristics (Y and Z generation) also positively and significantly impact employee engagement. Generational characteristics do not moderate the relationship between employee involvement and employee performance, but directly employee engagement and employee performance can be improved with generational characteristic variables. Organizational leaders should pay attention to employee engagement and the characteristics of the generation of employees and can make it a potential to improve employee performance.